(untitled) (American Journal of Data Science and Artificial Intelligence, 2025)
With an eye toward companies like Shoprite Nigeria, UBA Bank, Hilton Hotels Nigeria, and MTN Nigeria, this study looks at how robotics may enhance marketing efforts in Nigerian enterprises. The study adopted a descriptive survey methodology to gather data from 200 individuals chosen by a mix of purposeful and proportional stratified sampling. After a standardized questionnaire was sent, descriptive and inferential statistics were used to examine the responses. The findings reveal that improving consumer involvement, brand impression, and the general success of marketing initiatives depends mostly on robots. Improving operational efficiency and customer experience have been noted from technologies including interactive kiosks, automated customer service systems, and in-store service robots. Still, various obstacles high costs, limited technical knowledge, and client resistance limit the general acceptance of robotics in marketing. Strongly positive links between the usage of robotics and gains in marketing effectiveness, customer satisfaction, and brand perception were found by hypothesis testing. Conversely, problems integrating robotics were found to have a detrimental effect on marketing performance. The report advises companies to strategically invest in robots, encourage the growth of technical knowledge, inform the public to increase acceptability, implement policies supporting innovation, and set up systems for ongoing observation and feedback. Following these techniques can help businesses maximize robotics to support marketing initiatives, increase customer happiness, and get a competitive edge. These results have important ramifications for organizations in Nigeria and other comparable developing countries as they offer insightful analysis for those wishing to include robotics into their marketing plans.